Eksistensi Aksara Pegon : Media Penyebaran Ilmu Agama Di Demak Kota Wali Dengan Pendekatan Mix Method - Muhammad Abdul Rohman; Nurul Izati; Amir Khosim (Asyafina Akademik Press, 2022)
This study aims to determine the existence of Pegon script in students and students in Demak Regency as the “kota wali”, then also to know how to write and read Pegon script. Then Knowing the effect of reading and writing Pegon script with BTQ (Read Write Al-Qur'an) lessons which are mandatory local content for schools in Demak. this research district using Mix Method Analysis. The results of this study indicate the level of understanding of students and students about literacy development, there are high school students who still do not know much about the Pegon script. Most of them are junior high school students. However, Mts and MA schools have started to provide additional local content, nahwu shorof. How to read and write this script is quite easy. Here, in terms of reading and writing, it is necessary to pay attention to the rules and how to cooperate with the hijaiyah letters. The influence of BTQ (Read Write Al-Qur'an) lessons by reading and writing pegon script is that respondents who are able to read and write pegon script admit that this script is very useful when they want to increase fluency in reading the Qur'an.